(untitled) (Bangladesh Journal of Pharmacology, 2015)
We detected the expression of microRNA-132 in Chinese patient with liver cancer and evaluated down-regulation of microRNA-132 affect on cell growth and apoptotic of liver cancer cell. Twenty four patients with liver cancer and 24 normal patients were obtained from the 105th hospital of Peoples Liberation Army. We measured the expression of microRNA-132 in all selected patients using quantitative RTPCR (qRT-PCR). Lastly, cell growth and apoptotic of liver cancer Human liver cancer MHCC97H cells after anti-microRNA-132 transfection were evaluated using CCK?8 solution and annexin V-FITC and propidium iodide kit. There was significant suppression in microRNA-132 expression of exosome and whose liver cancer cell, comparison with normal patients. Down-regulation of microRNA-132 could inhibit cell growth and activated apoptotic of liver cancer cell. These findings indicate that microRNA-132 provides increased sensitivity of detection than normal patients. MicroRNA-132 may serve as a potential biomarker for treatment on liver cancer.